Applications of mini G proteins to study G protein-coupled receptors - Carpenter, Byron (Henry Stewart Talks, 2020)
Structure determination of G protein-coupled receptors (GPCRs) in their active state, Development of engineered mini G proteins, Applications of mini G proteins in GPCR structural studies, Crystallisation of the human adenosine A2A receptor in complex with a mini G protein, Applications of mini G proteins in GPCR functional studies